Smoke Mountain - Hunter, Erin. (New York : HarperCollinsPublishers, 2009)
Continues the journey of a black bear, a polar bear, and a grizzly cub in their search to find the Last Great Wilderness.
5.4
5-8
Keywords: Bears -- Juvenile fiction; Bears -- Fiction; Fantasy; Bears -- Fiction; Fantasy fiction